Análise de transmissão de preços do mercado atacadista de melão do Brasil - Mayorga, Rodrigo de Oliveira (2006)
The present study has the purpose to analyze the relationship among wholesale market of yellow melon in Brazil. Time series methods, unit root test, Johansen cointegration test, Vectorial Autoregressive models (VAR), variance decomposition of prediction error and impulse response function were used to analyze the price transmission among these markets. The analyzed period embraces January 2001 to December 2005. The results showed that, despite Açu/Mossoró-RN and baixo Jaguaribe-CE represents the national biggest melon production areas, wholesale prices deviations from the Supply Centers of Natal and Fortaleza, didn’t affect in a significant way the other markets studied. On the other hand, price variation of the CEAGESP - Companhia de Entrepostos e Armazéns Gerais de São Paulo, affects all the others wholesale markets analyzed. Therefore, the CEAGESP, representing national wholesalers, it being the biggest intermediary of the country, commands the Brazilian yellow melon market, establishing, in practice, an oligopolistic market. This means that, the CEAGESP wholesalers imposes the market prices, and that, Supply Centers of Natal, Fortaleza, Salvador, Recife, Curitiba, Belo Horizonte and Brasília are prices takers of the yellow melon wholesale market of Brazil.